The Relationship Between Internal Control And Compensation Appropriateness For Accounting Fraudulent Actions In Retail Companies - Aprillia, Frida; Supriyanto, Iwan; Handayani, Miranti; Sugiarti, Susie; Hartini , Dorit; Syah Putra, Arman (International Journal of Educational Research & Social Sciences, 2022)
The background of this research is how to find accounting fraud in a retail company, which consists of internal control variables and compensation suitability. Therefore, with accounting fraud, it can be prevented from an early age so that retail companies can continue to move forward in the future. The method used in this study is to use the literature review method and use quantitative methods by conducting a survey to 22 retail companies in order to find out frauds that exist in retail companies. The problem in this research is how to find out accounting fraud in a retail company that raises variables from internal control and compensation suitability with the two variables, it will be known what fraudulent actions occurred in retail companies so that retail companies can progress and develop so that they do not the loss is getting worse. The purpose of this study is how to find out accounting frauds in a retail company, because the fraud can make a retail company close and go bankrupt. Therefore, with preventive measures, it can be seen what things can prevent the company from cheating.